Piezoelectric performance of microbial chitosan thin film derived from aspergillus oryzae - Zamlia, Mohamad Izzuddin; Mohd Hatta, Maziati Akmal; Ahmad, Farah; Hisham, Firzanah (Diponegoro university Indonesia - Center of Biomass and Renewable Energy (CBIORE), 2022)
In this study, chitosan thin film derived from Aspergillus oryzae cell walls was fabricated and characterised. First, the chitosan from the fungal biomass was extracted (0.18 g/g) with 52.25% of degree of deacetylation obtained through Fourier transform infrared (FTIR) spectroscopy. Subsequently, several parameters of the chitosan thin film fabrication were optimised, including chitosan solution volume and drying temperature. Resultantly, the highest mechanical quality factor (3.22±0.012), the lowest dissipation factor (0.327±0.0003) and the best tensile strength (13.35±0.045 MPa) were obtained when pure chitosan was dissolved in 35 ml of 0.25 M formic acid and dried at 60 ˚C. In addition, the scanning electron microscopy (SEM) analysis presented a fine chitosan agglomerate distributed in the formic acid. The optimised fabricated, fungal-derived chitosan thin film was validated, recording a mechanical quality factor of 3.68 and dissipation factor of 0.248; both values were comparable to the synthetic polymer, polyvinylidene fluoride (PVDF) thin film. Thus, fungal-derived chitosan thin film can potentially be used as a piezoelectric material.